CHARACTERISTICS OF MANGO FRUIT LEATHER ( MANGIFERA INDICA ) WITH THE ADDITION OF LIME ( CITRUS AURANTIIFOLIA ) IN VARIATION OF DRYING TEMPERATURE - Andra Tersiana Wati; Diah Ayu Puspasari (Jurnal Pangan dan Agroindustri, 2023)
Mango is a fruit favorite of tropical people and oranges Lime is rich in vitamin C as well abundant available moment season harvest. As an easy commodity broken, needed innovation to get consumed moment no season harvest. Innovation possible processing one of them did fruit leather. Fruit leather is a product layer flt practica, durable and worth economical. Influence variation temperature drying (50 °C; 60 °C; 70 °C; and 80 °C) to characteristics physical that is color and texture as well as Vitamin C levels of fruit leather were observed with us the method Draft Random Complete (RAL) Non-Factorial. Therefore a sensory test was carried out on the resulting product on 25 panelists no trained . From the results research fruit leather mango with a temperature of 60 o C is sufficiently preferred with a content of vitamin C 1of 5.74 (mg/100 g) and water content of 11.59 (% db ) and texture 4365.58 g and color L = 53.81, a= 21.29, b = 48.58).